Translation shifts of compound-complex sentences in Arabic translation of Graham Greene’s The Tenth Man - Al-Shyiab, Monther Mohammad Ali (2024)
Translating compound-complex sentences (CCS) from English into Arabic is challenging due to the significant linguistic and cultural differences between the two languages. This study examines the translation strategies used to render CCS in Graham Greene’s The Tenth Man (TTM) into Arabic. A key difficulty for translators is finding suitable equivalents for CCS structures, as Arabic may lack direct counterparts, requiring strategies like translation shifts (TSs) to maintain meaning, syntax, and cultural nuances. Cultural elements, more resistant to translation than linguistic ones, often involve expressions unfamiliar to other languages, making translation even more complex due to lexical gaps between cultures.The present study aims to examine the extent to which the form/structure of CCS has been preserved in the Arabic translation of TTM considering the cultural and contextual elements present in the novel, to analyze the TSs employed in the Arabic translation of CCS in the book, taking into account the cultural nuances and contextual references within TTM and to assess the effectiveness of the TSs in conveying the meaning, structure, or form of the CCSs in the book, while addressing the cultural and contextual disparities that may impact translation fidelity.This study employs a mixed methods approach, combining qualitative and quantitative analysis. It involves a detailed examination of CCS from the original English novel and its Arabic translation. The analysis is grounded in Catford’s (1965) and House’s (1997- 2014) translation theories. A key finding highlights the translator’s effective use of Catford’s (TSs) to successfully translate CCS. Structural shifts were most prevalent, with word order alterations being the most common. They contributed significantly to maintaining syntactic cohesion and achieving textual equivalence. Unit and class shifts effectively adapted the translation to the TLs norms, ensuring linguistic accuracy and cultural appropriateness. Intra-system and level shifts although less frequent played a critical role in preserving meaning by accommodating grammatical and contextual nuances. Over 98% of shifts conveyed meaning effectivelyand about 63% maintained the original form, addressing cultural and contextual disparities effectively. TSs did not compromise meaning or cultural integrity. These strategies enable translators to navigate differences in grammar, syntax, semantics, and cultural contexts, ensuring accurate translations of meaning, form, and cultural significance. By applying (TSs), translators achieve both linguistic and cultural equivalence, maintaining fidelity to the source material while making the translation resonate with the target audience. The study’s findings contribute to a deeper understanding of the translation challenges, offer practical strategies for translators, bridge gaps in existing literature andextend its implications to translation theory, practice, and education. This study offers practical contributions by presenting a detailed taxonomy of the challenges in translating (CCS) and proposing strategies to address them. It also highlights educational implications, stressing the need for translation training programs to equip translators with the skills required to handle complex linguistic and cultural contexts effectively. It sheds light on the intricacies of translating CCS. The translator’s judicious use of TSs effectively conveyed the meaning and cultural context of the ST, highlighting the importance of cultural and linguistic sensitivity in translation.